Association between vitamin D status and thyroid cancer: a meta-analysis - Hu, Yue; Xue, Chongxiang; Ren, Shumeng; Dong, Lishuo; Gao, Jiaqi; Li, Xiuyang (Frontiers in Nutrition, 2024)
Background: Cumulative evidence has suggested that vitamin D deficiency is related with an increased susceptibility to various types of cancers. However, the association between vitamin D and thyroid cancer(TC) has remained to be unknown. Thus, there has been an urgent need for a metaanalysis to summarize existing evidence on vitamin D levels and the risk of TC.Objective: This meta-analysis aimed to figure out the association between vitamin D level and the risk of TC. Methods: A systematic search was performed for eligible articles on the association between vitamin D and TC based on PubMed, Embase, Web of Science, Cochrane, and ClinicalTrials.gov. Outcomes were the vitamin D level of cases with TC and the incidence of vitamin D deficiency in cases with TC comparing with the controls. The effect measures included standardized mean difference(SMD), ratio of means(RoM), and odds ratio(OR). A dose-response meta-analysis was performed to assess the correlation between vitamin D level and the risk of TC. Subgroup analyses and meta-regressions were conducted to explore the source of heterogeneity. And publication bias was evaluated through Begg's and Egger's tests. Results: Results of the meta-analysis revealed lower levels of vitamin D in TC cases comparing with those in control[SMD=-0.25, 95%CI: (-0.38, -0.12); RoM=0.87, 95%CI: (0.81,0.94)] and the levels of 1,25(OH)D in cases with TC were also lower than controls RoM=0.90, 95%CI: (0.85, 0.96)]. And vitamin D deficiency was associated with the increased risk of TC [OR=1.49, 95% CI: (1.23, 1.80)]. Additionally, results from the dose-response meta-analysis showed that there is a 6% increase in the risk of TC for each 10 ng/ml decrease in 25(OH)D levels[OR= 0.94; 95% CI: (0.89, 0.99)].Conclusions: Individuals with TC had lower levels of vitamin D compared to controls, and vitamin D deficiency was correlated with an increase risk of TC.